ESBL Producing Escherichia coli in Faecal Sludge Treatment Plants: An Invisible Threat to Public Health in Rohingya Camps, Cox's Bazar, Bangladesh - Hossain, Md. Sakib; Ali, Sobur; Hossain, Monir; Uddin, Salman Zahir; Moniruzzaman, M.; Islam, Mohammad Rafiqul; Shohael, Abdullah Mohammad; Islam, Md. Shafiqul; Ananya, Tazrina Habib; Rahman, Md. Mominur; Rahman, Mohammad Ashfaqur; Worth, Martin; et al. (Frontiers in Public Health, 2021)
Introduction: Human faecal sludge contains diverse harmful microorganisms, making it hazardous to the environment and public health if it is discharged untreated. Faecal sludge is one of the major sources of E. coli that can produce extended-spectrum β-lactamases (ESBLs). Objective: This study aimed to investigate the prevalence and molecular characterization of ESBL-producing E. coli in faecal sludge samples collected from faecal sludge treatment plants (FSTPs) in Rohingya camps, Bangladesh. Methods: ESBL producing E. coli were screened by cultural as well asmolecular methods and further characterized for their major ESBL genes, plasmid profiles, pathotypes, antibiotic resistance patterns, conjugation ability and genetic similarity. Results: Of 296 isolates, 180 were phenotypically positive for ESBL. All the isolates, except one, contained at least one ESBL gene that was tested (blaCTX-M-1, blaCTX-M-2, blaCTX-M-8, blaCTX-M-9, blaCTX-M-15, blaCTX-M-25, blaTEM, and blaSHV). From plasmid profiling, it was observed that plasmids of 1-211 MDa were found in 84% (151/180) of the isolates. Besides, 13% (24/180) of the isolates possessed diarrhoeagenic virulence genes. From the remaining isolates, around 51% (79/156) harbored at least one virulence gene that is associated with the extraintestinal pathogenicity of E. coli. Moreover, 4% (3/156) of the isolates were detected to be potential extraintestinal pathogenic E. coli (ExPEC) strains. Additionally, all the diarrhoeagenic and ExPEC strains showed resistance to three or more antibiotic groups which indicate their multidrug-resistant potential. ERIC-PCR differentiated these pathogenic isolates into seven clusters. In addition to this, 16 out of 35 tested isolates transferred plasmids of 32-112 MDa to E. coli J53 recipient strain. Conclusion: The present study implies that the faecal sludge samples examined here could be a potential origin for spreading MDR pathogenic ESBL-producing E. coli. The exposure of Rohingya individuals, living in overcrowded camps, to these organisms poses a severe threat to their health.